Cultivo de gránulo de kéfir en zumo de uvas tintas - Pedraza Guevara, Santos (2018)
This study is part of research developed in the area of ​​Food Science, Department of Analytical Chemistry and Food, University of Vigo Ourense Campus, Spain.; whose ultimate goal is to occurring fermented beverages with probiotic properties with kefir grains juice of red and white grapes would thus not valuing vinificables grapes with low commercial value or direct consumption. And obtaining healthy drinks combining ink effects mainly polyphenol grape character with antioxidant kefir and functional benefits. Kinetics main fermentation process cash studied, the effect of change on the fermentation substrate and microbial populations analyzed kefir. The procedure was carried out as follows: the pellet was activated, conducted a sequence of four successive crops. In each one the juice grain was incubated of nonsterile red grape during 24 h. The grain separated and juice fermented by fresh juice was replaced. At 12 hours of incubation and in the juice fermented after 24 h samples were taken, centrifuged to separate biomass from which the concentration of free cells and CFU of each of the 3 great microbial groups lactic acid bacterium was determined, acetic acid and yeast, and the supernatants were analyzed pH, sugars and metabolites by HPLC. Additionally samples at the beginning and end of each fermentation to determine counts BLA, BAC and LEV were taken. According to the obtained results, it seems logical to use the product fermented obtained for one double purpose. The beverage fermented juice kefir grains inks grapes, could be used as a new alcoholic beverage due to its high ethanol content (~ 33 g/L), after separation of the cells. The probiotic cells obtained with high viability could be used to occurring a food supplement, the potential benefits that their use might have on the health of consumers of the product. Biomass concentrations of free juice obtained during the first two passes, between 1 and 2 g/L, but in the third pass, a maximum value at about 6 g/L is obtained. This rise in the production of free biomass in the third pass, also corresponds with the increased consumption of sugars (glucose and fructose) from the third passage (subculture), possibly because at this stage and kefir grains were adapted to the composition of the fermentation medium again from the average activation. As for the formation of products, catches the eye, compared to whey crops, high yields of ethanol exceeding 4 times, the whey obtained full consumption and lactic acid medium fermentation, the total absence of acetic acid in addition to the production of significant amounts of glycerol from 2 g/L in the first pass to about 6 g/L, in the fourth pass. This suggests an increased activity of the population regarding yeast populations of lactic and acetic bacterium. The initial pH level of red grape juice (~ 3.8), suitable for the growth of yeasts and unsuitable for the development of lactic acid bacterium (LAB) and acetic acid (BAC) support this hypothesis. The disappearance of lactic acid from the fermentation medium suggests further use by the assimilating yeasts of this acid, a reconsumo by LAB due to high initial concentrations of sugars (glucose and fructose) in the fermentation.